School Transformation Through Learning-Driven Principal ‎Leadership: A Case Study in SD Negeri 1 Karangmulyo Kendal ‎Regency - Zayyinul Firdaus; Nurkolis; Ngasbun Egar (Yayasan Darussalam Bengkulu, 2026)
School transformation has become a strategic priority for improving educational quality; however, limited research has examined how transformation unfolds within Indonesian elementary schools led by Guru Penggerak principals. This study explored the process of school transformation at SD Negeri 1 Karangmulyo, Kendal Regency, using the Awareness–Exploration–Implementation–Sustainability (AEIS) framework as an analytical lens to examine how organisational change was experienced and interpreted by school stakeholders. A qualitative single-case study design was employed. Data were collected through semi-structured interviews with the principal, teachers, school committee members, parents, and students, complemented by observations and analysis of school documents. Interview interpretations were verified through member checking with participants, while triangulation across interviews, observations, and documentary evidence was used to strengthen the credibility and confirmability of the findings. Data were analysed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that participants described school transformation as an interconnected process in which shared awareness, collaborative exploration, implementation of agreed practices, and the institutionalisation of routine reflection supported organisational learning. Across all four stages, collaborative reflection and evidence-informed decision-making consistently connected planning, implementation, and evaluation. Rather than confirming the AEIS framework as originally conceptualised, the findings suggest that these collaborative mechanisms refine understanding of how transformation develops within the context of an Indonesian elementary school. The study proposes that collaborative reflection and evidence-informed leadership may support organisational learning in comparable school contexts, while recognising that the transferability of these propositions requires further investigation through longitudinal and multi-case research.